Physiologic Characteristics of Hyperosmolar Therapy After Pediatric Traumatic Brain Injury - Wellard, Jeffrey; Kuwabara, Michael; Adelson, P. David; Appavu, Brian (Frontiers in Neurology, 2021)
All work was performed at the Barrow Neurological Institute at Phoenix Children's Hospital. Objective: Investigate injury severity, neuroimaging, physiology, and outcomes with bolus hyperosmolar therapy (HT) of 3% hypertonic saline or mannitol. Methods: Retrospective cohort analysis was performed. Physiologic variables included intracranial pressure (ICP), arterial blood pressure (ABP), and heart rate (HR). Volume-pressure compensation (PVC) indices included ICP pulse amplitude (AMP) and correlation of AMP and ICP (RAP). Cerebrovascular pressure reactivity (CVPR) indices included pressure reactivity index (PRx), pulse amplitude index (PAx), wavelet PRx (wPRx), and correlation of AMP and cerebral perfusion pressure (RAC). Heart rate variability (HRV) indices included heart rate standard deviation (HRsd), heart rate root mean square of successive differences (HRrmssd) and low-high frequency ratio (LHF). Outcome was assessed using Glasgow Outcomes Scale Extended Pediatrics, 12-months post-injury. Generalized estimating equations was applied to investigate associations of physiologic changes and pre-treatment indices with HT efficacy. Repeated measures analysis of variance was applied to investigate changes after HT without intracranial hypertension (ICH). Wilcoxon rank-sum was applied to investigate HT responsiveness with age, injury severity, neuroimaging, and outcomes. Results: Thirty children received bolus HT. ICH reduction after HT was associated with reduced ICP (p = 0.0064), ABP (p = 0.0126), PRx (p = 0.0063), increased HRsd (p = 0.0408), and decreased pretreatment RAC (p = 0.0115) and wPRx (p = 0.0072). HT-responsive patients were older and had improved outcomes (p = 0.0394). HT without ICH was associated with increased ICP (P < 0.0001) and ABP (P < 0.0001), increases in all HRV indices and decreases in all PVC indices. Conclusion: After pediatric TBI, efficacious HT is associated with decreased ICP and ABP, pre-treatment indices suggesting efficient CVPR, and potentially improved outcomes.